THE INTER-LEVEL ANALYSIS OF QUANTITATIVE UNITS IN UZBEK AND ENGLISH LANGUAGES (Scientific journal of the Fergana State University, 2025)
This article provides an in-depth analysis of the expression and inter-level manifestation of quantitativeness in Uzbek and English. The study thoroughly examines the possibilities of expressing quantitativeness at the phonetic, morphological, lexical, and phraseological levels, identifying similarities and differences between the two languages. The functional characteristics of the means used to express quantitativeness are also analyzed. The research highlights the potential for quantitativeness to manifest at other linguistic levels, which is evaluated as a complex linguistic phenomenon. The results contribute to understanding the scientific significance and role of quantitativeness in linguistics. Moreover, the article enables a comparative evaluation of the unique features of the system of expressing quantitativeness in Uzbek and English. This research serves as a theoretical and practical foundation for studying quantitativeness across various linguistic levels. The work introduces new approaches to linguistic studies and holds significant value for further research in this field. The article is aimed at identifying commonalities and distinctions between the two languages in expressing quantitativeness at different linguistic levels.